2021
DOI: 10.1021/acsmaterialslett.1c00135
|View full text |Cite
|
Sign up to set email alerts
|

Spindle Single-Crystalline Rutile TiO2 with Excellent Cyclability for Low-Cost Li-Storage Materials

Abstract: We investigated the Li storage properties of spindle single-crystalline rutile TiO 2 fine particles synthesized by a large-scale sulfate process. Their anode properties were compared with those of polycrystalline rutile TiO 2 particles. An increase in the degree of single-crystal formation improved the charge−discharge capacity and initial Coulombic efficiency. In situ X-ray diffraction and transmission electron microscopic observation demonstrated the structural integrity of the spindle particles during the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 27 publications
2
45
0
Order By: Relevance
“…24 A large slope in the low potential region obtained during the first lithiation process is a typical feature of rutile TiO2 electrodes. [10][11][12][13][14][15][16][18][19][20] The initial discharge capacity was 257 mAh g −1 , and the charge-discharge curves of the second and third cycles were fully consistent with each other, indicating high reversibility of the electrode reactions. The electrode capacity was maintained at 220 mAh g −1 until the 10th cycle (Fig.…”
Section: Tio 2 Phase Changementioning
confidence: 72%
See 3 more Smart Citations
“…24 A large slope in the low potential region obtained during the first lithiation process is a typical feature of rutile TiO2 electrodes. [10][11][12][13][14][15][16][18][19][20] The initial discharge capacity was 257 mAh g −1 , and the charge-discharge curves of the second and third cycles were fully consistent with each other, indicating high reversibility of the electrode reactions. The electrode capacity was maintained at 220 mAh g −1 until the 10th cycle (Fig.…”
Section: Tio 2 Phase Changementioning
confidence: 72%
“…16 The authors of this work focused on the impurity doping and high crystallization degree of rutile TiO2. [18][19][20] We performed Nb doping of rutile TiO2 18 and demonstrated that a Nb-doped TiO2 electrode exhibited a very high rate capability of 120 mAh g -1 even at a high rate of 50C. 19 In addition, we achieved an outstanding cyclability with 170 mAh g -1 during 5500 cycles at 1C by using single-crystalline rutile TiO2.…”
Section: Accepted M Manuscriptmentioning
confidence: 95%
See 2 more Smart Citations
“…Li + , Na + , K + , Zn 2+ , and other metal ion hybrid energy storage systems have emerged and attracted widespread interest with the rapid development of renewable energy. Compared with the limitations of Li + and Na + as well as K + nonaqueous energy storage systems, it is noted that aqueous zinc-ion batteries (ZIBs) and zinc-ion hybrid supercapacitors (ZHSs) have particularly attracted numerous attention because of their high capacity, low redox potential, safety, and environmental friendliness. Among these systems, ZHSs are constructed with a battery-type anode (Zn electrode) and capacitive cathode materials. , Therefore, they combine the energy storage mechanism of supercapacitors and batteries into one system and possess merits of high energy and power densities, giving broad application prospects in mobile communications and electronic equipment. , Despite all the advantages and research interest in ZHSs, the excellent performance of ZHSs largely depends on seeking for cathode materials with high capacity and stable structures.…”
Section: Introductionmentioning
confidence: 99%